2022
DOI: 10.1161/jaha.121.022257
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Blood Pressure and Accelerated DNA Methylation Aging

Abstract: Background Individuals of the same chronological age may exhibit diverse susceptibilities to death. However, few studies have investigated the associations between blood pressure and the accelerated aging. Methods and Results A cross‐sectional study was conducted in 288 adults aged ≥50 years. We assessed the DNA methylation‐based measures of biological age using CpG sites on the Illumina HumanMethylationEPIC BeadChip. Epigenetic age accel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 47 publications
3
9
0
Order By: Relevance
“…It is undeniable that most studies have focused on mid- to end-of-life applications, and data from early-life interventions are sparse and require a more robust evaluation. Additionally, we found that elevated PP and the presence of hypertension or diabetes were potential effect modifiers as well, possibly because these states inherently accelerate senescence [ 59 , 60 ]. The enhanced senescence of renal tubules and vascular cells leads to endothelial dysfunction and impaired vasculogenesis [ 61 ], suggesting the presence of complex physiologically relevant feedback loops.…”
Section: Discussionmentioning
confidence: 99%
“…It is undeniable that most studies have focused on mid- to end-of-life applications, and data from early-life interventions are sparse and require a more robust evaluation. Additionally, we found that elevated PP and the presence of hypertension or diabetes were potential effect modifiers as well, possibly because these states inherently accelerate senescence [ 59 , 60 ]. The enhanced senescence of renal tubules and vascular cells leads to endothelial dysfunction and impaired vasculogenesis [ 61 ], suggesting the presence of complex physiologically relevant feedback loops.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, two previous studies demonstrated that the alcohol use disorder was associated with Horvath’s age acceleration and PhenoAge acceleration (PAA) [ 19 , 20 ]. Hypertension, which was often linked to chronic alcohol consumption, was also found to be positively associated with Horvath’s age acceleration in the elderly [ 21 , 22 ]. The hypertensive target organ damage (e.g., higher left ventricular mass index) was also associated with Intrinsic epigenetic age acceleration (IEAA) and extrinsic epigenetic age acceleration (EEAA) in older African Americans [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Blood pressure exhibits alterations with advancing age, generally characterized by an increase in systolic pressure while diastolic pressure remains stable or even reduces, potentially associating these periodic dynamic changes in blood pressure with biological aging. Research by Xiao et al ( 57 ) disclosed that higher systolic and pulse pressures are related to accelerated epigenetic aging. Dintica et al ( 58 ) proposed that elevated blood pressure during middle age associates with premature brain aging.…”
Section: Discussionmentioning
confidence: 99%